Pengaruh Keadilan Organisasi Terhadap Kinerja Karyawan yang Dimediasi oleh Komitmen Organisasi - Sarianti, Rini; Mesta, Hendri Andi; Sari, Mayang (Jurnal Kajian Manajemen Bisnis, 2017)
The purpose of this research is to analyze: (1) The effect of organizational justice on employee performance PT. Andalas Berlian Motors Branch Simpang Empat, (2) The effect of organizational justice on organizational commitment of employees of PT. Andalas Berlian Motors Branch Simpang Empat, (3) Effect of organizational commitment on employee performance PT. Andalas Berlian Motors Branch Simpang Empat, (4) The effect of organizational justice on employee performance as mediator organizational commitment PT. Andalas Berlian Motor Branch Simpang Empat. The population in this researchis were all employees of PT. Andalas Berlian Motors Branch Simpang Empat, the sampling technique is total sampling technique with a sample of 31 employees of PT. Andalas Berlian Motors Branch Simpang Empat. Based on the results of this research is concluded that (1) Organizational justice have significant effect on employees performance of PT. Andalas Berlian Motors Branch Simpang Empat, (2) Organizational justice have significant effect on organizational commitment of employees PT. Andalas Berlian Motors Branch Simpang Empat, (3) Organizational Commitment have significant effect on employees performance of PT. Andalas Berlian Motor Branch Simpang Empat, (4) There is significant effect of organizational commitment as mediator organizational justice on employee performance PT. Andalas Berlian Motors Branch Simpang Empat.Â Keywords:Employee Performance, Organizational Commitment, Organizational Justice